Pengembangan Bahan Ajar Teks Ceramah Berbasis E-Book dengan Pendekatan Kearifan Lokal dalam Meningkatkan HOTS Siswa Kelas XI Sekolah Menengah Atas Negeri 2 Lubuk Pakam - Nurul Febyanti; Liesna Andriany; Nila Safina; Ali Ali; Rita Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The need for innovative teaching materials that integrate local wisdom and support meaningful learning in sermon text instruction encouraged the development of an e-book designed for Grade XI students. This study aimed to develop and assess the feasibility of local wisdom-based e-book teaching materials on sermon texts, as well as to evaluate teacher and student responses toward their use at State Senior High School 2 Lubuk Pakam. The population consisted of 394 students, with 69 students from classes XI I and XI J selected as the sample. This study employed a Research and Development (R&D) approach using Thiagarajan’s 4D model, which includes the stages of define, design, develop, and disseminate. The results indicated that the developed teaching materials were feasible for instructional use. Content Expert I assigned a score of 85.3% (Feasible), while Content Expert II assigned 81.3% (Feasible). Design Expert I assigned 90.6% (Highly Feasible), and Design Expert II assigned 80% (Feasible). The Indonesian language teacher’s response reached 96% (Highly Feasible), while student responses reached 89% (Highly Feasible). Interview data further supported the positive reception of the product. The developed e-book provides contextual learning resources that integrate local wisdom into sermon text instruction and support learning activities oriented toward higher-order thinking. Therefore, the product is feasible as a supplementary learning resource for sermon text learning in senior high schools.